Answer:
2.(b) w= 3
3. x= -3 or x= 3
Explanation:
2.(b) Method 1:
![(2w - 1)/(5) + w + 2 = 2w \\ (2w - 1)/(5) = 2w - w - 2 \\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/iw0ite5u6gju4ryixsfaos3qibz30w85nt.png)
Simplify:
![(2w - 1)/(5) = w - 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j5zh3eeuo38l8dkenwz7q1y5pjvfdz2ck7.png)
×5 on both sides:
![2w - 1 = 5(w - 2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/kh9701pgsny4ug8f4kmz0q4bx17m3987gv.png)
Expand:
![2w - 1 = 5w - 10](https://img.qammunity.org/2021/formulas/mathematics/middle-school/abojqaqdy05n8busg22h7f1c6slrc4uei6.png)
Bring constants to 1 side, w terms to the other:
![5w - 2w = 10 - 1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j29ts447acoia4lw2sduevzu3rmc79u6w8.png)
Simplify:
![3w = 9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4acxetsfhfqy2fz6ij8wkwbpps7ru4nslu.png)
Divide both sides by 3:
![w = 9 / 3 \\ w = 3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mt2whegvs9fnm5re0jvsvm2qtrquuoblnl.png)
Method 2:
![(2w - 1)/(5) + w + 2 = 2w](https://img.qammunity.org/2021/formulas/mathematics/middle-school/bvub07c52wobr97r12l4zzbcclhscn5uou.png)
Multiply by 5 throughout:
![2w - 1 + 5(w + 2) = 5(2w)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tth3h6smxigwdaatzbvq9w6ml641kzqlx4.png)
Expand:
![2w - 1 + 5w + 10 = 4w](https://img.qammunity.org/2021/formulas/mathematics/middle-school/lrm59h6g95ys3312toa9ch8tdoac7n3zxx.png)
Simplify:
![7w - 9 = 4w](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e8mf73vmuoyf7lwzkdnxd1fkbzwarurnrx.png)
+9 on both sides:
![7w = 4w + 9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qhtaj2q8k8hw27crhu8xvlguxe3m8hw34z.png)
-4w on both sides:
![7w - 4w = 9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v5r12hsgfg4b84wfrwnk0odlhvah9sse9q.png)
Simplify:
![3w = 9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4acxetsfhfqy2fz6ij8wkwbpps7ru4nslu.png)
Divide by 3 on both sides:
![w = 3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/cs2fgmnx0vstoodkb82z5p51cg2xw4dhtj.png)
3.
![(6x - 12)/(3) + 4 = (18)/(x)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/gq95ap20vkxmww6yzqga5a6xx8neuxas76.png)
Multiply by 3x on both sides:
![(3x(6x - 12))/(3) + 3x(4) = (3x(18))/(x) \\ x(6x - 12) + 12x = 3(18)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/d5360f20mou7tsjry8w3935bxqr785rpjh.png)
Expand:
![x(6x) - x(12) + 12x = 54 \\ 6x^(2) - 12x + 12x = 54 \\](https://img.qammunity.org/2021/formulas/mathematics/middle-school/9ig6ncpkywjrdlywuvtgwvxjpoa5wob72m.png)
Simplify:
![6 {x}^(2) = 54](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p6m8e4lmhni33dagw99lnfzododzvqimig.png)
Divide by 6 on both sides:
![{x}^(2) = 9](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hew6hvkz3sh8jyutqd12agyj6atal8ifgp.png)
-9 on both sides:
![{x}^(2) - 9 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/enp5j6dytkp381nc15m8g8bzci6hqrb46o.png)
Factorise:
*Since a²-b²= (a +b)(a -b),
![{x}^(2) - {3}^(2) = 0 \\ (x + 3)(x - 3) = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/tsucrk96vuuwuulhi2w4535px2cgjqe0p9.png)
Thus,
x +3= 0 or x -3= 0
x= -3 or x= 3